Developing Metacognitive Skills in Mathematics Learning through Integration with Other Disciplines (STEM, Socio-Cultural Methods) - Juliana Artanti; Wildani Wildani (Gema Cendekia Institute, 2025)
This study aims to develop students' metacognitive skills in mathematics learning through integration with other disciplines, specifically the Science, Technology, Engineering, and Mathematics (STEM) approach and socio-cultural methods. Metacognitive skills are considered important because they play a role in increasing students' awareness of thinking processes, problem-solving strategies, and reflective abilities in learning. The research method used is development research with a multidisciplinary integration-based learning design model. The research subjects consisted of high school students who took mathematics lessons on the topics of geometry and contextual problem solving. Data were collected through metacognitive skills tests, observation sheets, and in-depth interviews. The results of the study indicate that the integration of mathematics with the STEM approach provides a more applicable learning experience, while the application of socio-cultural methods enriches students' understanding through local context and collaboration. Overall, the application of this integration-based learning has been proven to improve students' planning, monitoring, and self-evaluation skills in solving mathematical problems. These findings recommend the need to develop a mathematics learning model that combines multidisciplinary and cultural aspects to foster stronger metacognitive abilities, relevant to the challenges of the 21st century)